Freshwater bacterial lifestyles inferred from comparative genomics. (26th July 2013) - Livermore, Joshua A.; Emrich, Scott J.; Tan, John; Jones, Stuart E.
Summary While micro‐organisms actively mediate and participate in freshwater ecosystem services, we know little about freshwater microbial genetic diversity. Genome sequences are available for many bacteria from the human microbiome and the ocean (over 800 and 200, respectively), but only two freshwater genomes are currently available: the streamlined genomes of Polynucleobacter necessarius ssp. asymbioticus and the Actinobacterium AcI‐B1. Here, we sequenced and analysed draft genomes of eight phylogentically diverse freshwater bacteria exhibiting a range of lifestyle characteristics. Comparative genomics of these bacteria reveals putative freshwater bacterial lifestyles based on differences in predicted growth rate, capability to respond to environmental stimuli and diversity of useable carbon substrates. Our conceptual model based on these genomic characteristics provides a foundation on which further ecophysiological and genomic studies can be built. In addition, these genomes greatly expand the diversity of existing genomic context for future studies on the ecology and genetics of freshwater bacteria.